The Promise of Education in Indonesia - World Bank (World Bank, Washington, DC, 2020)
This Indonesia Education Flagship Report examines ways to strengthen education reforms and boost the learning outcomes of all Indonesian students. It focuses on how the education system can deliver on the promise of human capital for Indonesia. The recommendations focus on protecting and building human capital by increasing the capacity, equity, and accountability for learning. The report also explores what the central government can do to make changes for the better in areas under its control and how to provide better guidance and support to provinces, districts, and schools.